Pemetaan Pola Sebaran Lokasi Lembaga Kursus Bahasa Asing di Kampung Inggris Menggunakan Sistem Informasi Geografis (SIG) - Ovarina, Yasfina Okta (Jurnal Vokasi Teknik Sipil, 2023)
This study aims to determine the mapping and distribution pattern of the location of foreign language course institutions in Kampung Inggris. This research is a quantitative study and the samples of this study are 133 foreign language course institutions in Kampung Inggris. The data collection technique used was to conduct an observation to find out the coordinates of the course institutions and conduct interviews to find the course institution data and administrative maps of the research sites. The method used is descriptive analysis to create a location distribution map using ArcGis 10.8 software and nearest neighbor analysis to look for its pattern of location distribution by calculating the T value or nearest neighbor distribution index. The calculated T value of 1,476 is a uniform pattern. This value is included in a uniform pattern because it is close to the value of 2.15.